METAMORFOSIS KOGNITIF: MENGOPTIMALKAN PEMAHAMAN KIMIA MELALUI METODE NUMERASI-VISUAL TERINTEGRASI UNTUK MAHASISWA 3T - Yosephine Debbie Damayanti; Andre Patanda (Jurnal Media Informatika, 2025)
This study examines the effectiveness of the numeracy-visual integrative learning method in improving students' understanding of chemical equilibrium. The subjects of the study consisted of 42 students from Lanny Jaya and Nduga, Papua. A quasi-experimental method with pre-test and post-test was used to measure the increase in understanding. The results showed a significant increase from an average pre-test score of 45.2 to 78.6 on the post-test (t(41) = 12.35, p < 0.001). Students' responses to this method were positive, with an average score of 4.3 out of 5 based on a Likert scale questionnaire. Some of the obstacles faced were limited access to technology and initial difficulties in understanding graphs. Overall, this method is effective in improving understanding of the concept of chemical equilibrium and can be applied in areas with limited learning resources.